Assessing the Effects of Ocean Warming and Acidification on the Seagrass Thalassia hemprichii - Liu, Pi-Jen; Chang, Hong-Fong; Mayfield, Anderson B.; Lin, Hsing-Juh (Journal of marine science and engineering, 2022)
Seagrass beds serve as important carbon sinks, and it is thought that increasing the quantity and quality of such sinks could help to slow the rate of global climate change. Therefore, it will be important to (1) gain a better understanding of seagrass bed metabolism and (2) document how these high-productivity ecosystems are impacted by climate change-associated factors, such as ocean acidification (OA) and ocean warming (OW). A mesocosm-based approach was taken herein in which a tropical, Western Pacific seagrass species Thalassia hemprichii was cultured under either control or OA-simulating conditions; the temperature was gradually increased from 25 to 31 °C for both CO2 enrichment treatments, and it was hypothesized that this species would respond positively to OA and elevated temperature. After 12 weeks of exposure, OA (~1200 ppm) led to (1) increases in underground biomass and root C:N ratios and (2) decreases in root nitrogen content. Rising temperatures (25 to 31 °C) increased the maximum quantum yield of photosystem II (Fv:Fm), productivity, leaf growth rate, decomposition rate, and carbon sequestration, but decreased the rate of shoot density increase and the carbon content of the leaves; this indicates that warming alone does not increase the short-term carbon sink capacity of this seagrass species. Under high CO2 and the highest temperature employed (31 °C), this seagrass demonstrated its highest productivity, Fv:Fm, leaf growth rate, and carbon sequestration. Collectively, then, it appears that high CO2 levels offset the negative effects of high temperature on this seagrass species. Whether this pattern is maintained at temperatures that actually induce marked seagrass stress (likely beginning at 33–34 °C in Southern Taiwan) should be the focus of future research.